Technology diffusion through production process and the innovative capacity of local suppliers - Abd Rahim Jaguli,; Marlin Marissa Malek,; Mohd Rizal Palil, (Penerbit Universiti Kebangsaan Malaysia, 2014)
This study goes beyond the existing research in the area of Foreign Direct Investment (FDI) spillovers by opening the black box of Multinational Corporations’ (MNC) technology and knowledge spillovers in Malaysia. The main objective of this study was to add to limited evidence related to how and in what ways technology and knowledge are diffused. Specifically, it attempts to contribute to the FDI spillover literature by exploring the channels through which technology and knowledge could be transferred to the host country. In doing so, the authors had employed an in-depth case study method in order to generate a deeper understanding of the significance of the assistance provided by MNCs and that this method would prove an effective strategy in generating a large volume of very meaningful data. The study has identified that technology is diffused from MNCs to local suppliers through the production process, technical consultation and production facilities. Local suppliers enhance their innovative capacity through these linkages. The findings not only provide benefit to the academic circle but also to local businesses, especially small and medium industries, as well as policy makers. The managerial and policy implications derived from the findings are relevant, not only to Malaysia, but also to other developing countries, particularly Malaysia’s neighbouring countries.